(untitled) (American Journal of Islam and Society, 2025)
The volume The Practice of Islam in America, edited by Edward E. Curtis, was released in 2017. It was an important work because it was a volume that took American Muslim ritual life as an primary source of study. It helped explain rituals and explored their manifestations in a variety of American Muslim contexts. Since then, there have been very few works on American Muslim ritual life. In the interests of transparency, I should note that both Rose Aslan and I contributed chapters to that volume. Aslan’s piece was on prayer, based on the work she was doing for the volume under review. Her monograph is a welcome addition to the exploration of American Muslim ritual life.